Drop analysis and numerical simulation of spent fuel transfer basket - Jiaojiao Dong; Chen Wang; Xiaogang Xu; Siqi Zhu (International Journal of Advanced Nuclear Reactor Design and Technology)
The spent fuel transfer basket is responsible for the transfer and storage of the assemblies, and the fall condition of the basket needs to be considered to ensure the critical safety of the spent fuel assemblies during the operation process. According to the actual process, two working conditions are assumed, i.e. vertical fall of the basket at a height of 1 m from the bottom of the pool in the air condition and tipping over underwater. The key parameters in the numerical simulation are verified by carrying out experiments to obtain numerical simulation results with high accuracy. Aiming at the tipping process which is greatly influenced by the fluid resistance, the underwater tipping test of the 1:2 model of the basket is carried out to obtain the influence of the fluid on the tipping of the basket and to obtain the equivalent fall angle of the tipping fall in the air of the basket. The equivalent stiffness of the assemblies in the model is corrected by the 1:1 model 1-m vertical drop test, and the corrected numerical simulation agrees well with the experimental results, which indicates that the drop calculation model obtained in this study can be applied to the actual design.